2010
DOI: 10.4028/www.scientific.net/amr.168-170.1046
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Simulation on Three-point Bending of Brazed Aluminum Honeycomb Panel

Abstract: The mechanics behaviors on three-point bending of brazed aluminum honeycomb panel by FEM are investigated in this paper. The results show that honeycomb panel have three typical failure modes under bending load:failure of honeycomb core collapse, the whole panel bending failure and face sheet shear failure. Honeycomb lateral bending failure load is greater than the longitudinal bending failure load. When the ratio of honeycomb core thickness and panel thickness is between 10% to 15%, the strongest cellular pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Simultaneously, Paik et al [14] comprehensively summarized the properties under out-of-plane and in-plane compression and bending conditions and developed the corresponding strength prediction formulas and equivalent methods. In addition to compression properties, the bending properties of aluminum honeycomb plates [15][16][17] are also research topics attractive to numerous scholars. However, the mechanical properties, failure modes, and strength of a GAHP are quite different from those of a BAHP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, Paik et al [14] comprehensively summarized the properties under out-of-plane and in-plane compression and bending conditions and developed the corresponding strength prediction formulas and equivalent methods. In addition to compression properties, the bending properties of aluminum honeycomb plates [15][16][17] are also research topics attractive to numerous scholars. However, the mechanical properties, failure modes, and strength of a GAHP are quite different from those of a BAHP.…”
Section: Introductionmentioning
confidence: 99%
“…As a new type of aluminum honeycomb plate, only limited research data are available on BAHPs. For example, Peng [15] conducted finite element analysis (FEA) to study the three-point bending properties of a BAHP as well as compared the effects of different unit cell thicknesses on the failure modes. Cai et al [10] simply compared the peeling stresses of a GAHP and a BAHP and suggested that the strength of a brazed connection is better than glued one.…”
Section: Introductionmentioning
confidence: 99%